Vous êtes sur la page 1sur 1

Caso Retangular

Considerações:

𝑑ℎ = 2 tan 𝛼 𝑑𝑥
𝜎0′ = 𝜎𝑥 + 𝑝 → 𝜎𝑥 = 𝜎0′ − 𝑝 → 𝑑𝜎𝑥 = −𝑑𝑝

∑ 𝐹𝑥 = 0

−𝜎𝑥 (ℎ𝑤) + (𝜎𝑥 + 𝑑𝜎𝑥 )(ℎ + 𝑑ℎ)𝑤 + 2𝑝 tan 𝛼 𝑑𝑥 𝑤 − 2𝜏 𝑤𝑑𝑥 = 0


−𝜎𝑥 ℎ + 𝜎𝑥 ℎ + 𝜎𝑥 𝑑ℎ + ℎ𝑑𝜎𝑥 + 𝑑𝜎𝑥 𝑑ℎ + 2𝑝 tan 𝛼 𝑑𝑥 𝑤 + 2𝜇𝑝𝑑𝑥 = 0
𝜎𝑥 𝑑ℎ + ℎ𝑑𝜎𝑥 + 𝑑𝜎𝑥 𝑑ℎ + 2𝑝𝑑𝑥(tan 𝛼 + 𝜇) = 0
𝜎𝑥 𝑑ℎ + ℎ𝑑𝜎𝑥 + 2𝑝𝑑𝑥(tan 𝛼 + 𝜇) = 0
𝜎𝑥 2 tan 𝛼 𝑑𝑥 + ℎ𝑑𝜎𝑥 + 2𝑝𝑑𝑥(tan 𝛼 + 𝜇) = 0
ℎ𝑑𝜎𝑥 + 2𝑑𝑥(𝑝[tan 𝛼 + 𝜇] + 𝜎𝑥 tan 𝛼) = 0
−ℎ𝑑𝜎𝑥 = 2𝑑𝑥(𝑝[tan 𝛼 + 𝜇] + 𝜎𝑥 tan 𝛼) = 0
𝑑𝜎𝑥 2𝑑𝑥
− =
(𝑝[tan 𝛼 + 𝜇] + 𝜎𝑥 tan 𝛼) ℎ
𝑑𝑝 2𝑑𝑥
′ =
(𝑝[tan 𝛼 + 𝜇] + (𝜎0 − 𝑝) tan 𝛼) ℎ
𝑑𝑝 2𝑑𝑥
′ =
(𝑝 tan 𝛼 + 𝜇𝑝 + 𝜎0 tan 𝛼 − 𝑝 tan 𝛼) ℎ
𝑑𝑝 2𝑑𝑥
′ =
(𝜇𝑝 + 𝜎0 tan 𝛼) ℎ
𝑑𝑝
(𝜇) 2𝑑𝑥
′ =
𝜎 tan 𝛼 ℎ
(𝑝 + 0 𝜇 )

𝑑𝑝 2𝜇𝑑𝑥
′ =
𝜎 tan 𝛼 ℎ
(𝑝 + 0 𝜇 )